Analysis of Environment Management on The Case of Dengue Fever in Sukomoro Sub-district, Magetan District - Djoko Windu P. Irawan; Denok Indraswati; Vincentius Supriyono; Trimawan Heru Wijono; Bambang Sunarko (Humanistic Network for Science and Technology (HNST), 2017)
Dengue Haemorrhagic Fever (DHF) is still a serious health problem because it is endemic and often attacks the community. A comprehensive approach to the prevention of DHF cases should take into account the physical, biological, social and management aspects of the environment. The objectives of the study was to analyze the environmental management and environmental relationship to DHF incident in Sukomoro Sub-district, Magetan District. This study was observational with cross sectional design. The sample were head of family in endemic and non endemic areas, totally 100 head of family. Methods of data analysis used in the study were frequency, Chi-square and Kendall Concordance Coefficient test. The results were: 1) there was no relationship between occupant density, daytime sleeping habits, cleaning habits of water reservoirs, community participation in mosquito nest eradication with DHF incidence, 2) there was a relationship between moisture, place of breeding, resting place, larva, habit of hanging cloth, and physical, biological, and social environmental factors with DHF. Conclusion: physical, biological, and social environmental factors are related to the incidence of DHF. The implementation of environmental management still needs improvement in the aspect of cadre development and the making of work plan and its implementation. Keywords: Environmental management, Dengue Hemorrhagic Fever